A Study of some the optical properties for (SnO2) thin films prepared by Sol-Gel method - Mohammed , Ban K. (Iraqi Journal of Science, 2022)
In this research a bilateral tin oxide (SnO2) thin films was prepared by Sol-Gel method, flow coating technique which is considered a simple and cheaptechnique. The horizontal sample preparation with and without the use ofinstalled, and also with installed to vertical sample. Results of opticalspectroscopy that the biggest values of the transmittance T was for horizontalfilms with an installed, as for the absorbance A was the biggest values of thevertical sample. For the reflectivity R was value in the horizontal films withinstalled, less than a horizontal films without Sticky as well as for filmsvertical. The results of the energy gap Eg for that direct allowed and forbiddentransitions and for the indirect allowed and forbidden transfers for the studiedSamples were also calculated, and they showed that the highest value of Eg was(3.85eV) for the direct forbidden transfers in the horizontal sample withinstaller, while the lowest value of Eg was (3.65eV) for the indirect allowedtransfers without installer. The vertical film with indirect showed the lowestvalue for the energy gap ever (3.45eV) for the indirect allowed transitions.